Morphological efficacy evaluation of gel with carbon dioxide extract of hops in case of complicated wound infection acne vulgaris - Moiseienko, T. M.; Torianyk, I. I.; Khrystian, G. Ye.; Rybak, V. A.; Voronkina, I. A.; Melnyk, A. L.; Merkulova, N. F.; Mohylenets, O. I.; Solomennyk, G. O.; Popova, N. G.; Ivannik, V. Yu.; Myroshnychenko, M. S.; et al. (Poland: ALUNA, 2021)
The aim of the study is to reveal in the experiment the morphological features of the infected skin wounds healing, which are a manifestation of acne vulgaris severe and very severe forms, using a gel with carbon dioxide extract of hops. Materials and methods: An experimental study was carried out on 80 male WAG rats of three months of age. The animals were divided into 9 groups. Group 1 consisted of intact animals (n=6). Group 2 was represented by animals (n=6), which had hair epilation on the dorsal surface of the body in an area of 1 сm2, followed by application of 2 ml of placebo gel to this area. Group 3 included animals (n=6), which were epilated on the dorsal surface of the body in an area of 1 сm2 and applied 2 ml of 1 % gel with carbon dioxide extract of hops. Group 4 included rats (n=6), which were epilated on the dorsal surface of the body in an area of 1 сm2 and simulated thermal damage. Group 5 was represented by 10 rats, who were epilated on the dorsal surface of the body in an area of 1 сm2, simulated thermal damage, followed by applying 2 ml of placebo gel to the wound surface. Group 6 included rats (n=10), who underwent measures similar to group 5, followed by application of 2 ml of 1 % gel with carbon dioxide extract of hops to the wound surface. In group 7, there were 6 rats, which were epilated on the dorsal surface of the body in an area of 1 сm2, thermal damage to the skin with underlying soft tissues was simulated, followed by application to the wound surface the reference strains of Staphylococcus aureus, Streptococcus pyogenes, Proteus vulgaris, Propionibacterium acnes, Escherichia coli, Pseudomonas aeruginosa, Malassezia slooffiae, Malassezia pachydermatis, Candida albicans, Candida parapsilosis. In groups 8 and 9, there were 15 rats each, which underwent measures similar to group 7, followed by applying 2 ml of placebo gel on its surface on the next day after infection of the wound in group 8, and in group 9 – 2 ml of 1 % gel with carbon dioxide extract hops. The material for the study was the skin with underlying soft tissues. It was used histological, histochemical, morphometric and statistical methods. Results: This experimentally created gel with carbon dioxide extract of hops activates separation processes of horny masses from the surface of the epidermis, cleaning the pores of the skin; stimulating the proliferative activity of the epidermis, which is located in the marginal sections of the wound or covers the surface of the regenerate; activating the processes of cleansing the wound from necrotic tissue; activating the growth and maturation of granulation tissue with its subsequent transformation into connective tissue. It has anti-inflammatory, bactericidal and antimycotic effects, normalizing skin microbiocenosis. Conclusions: The complex morphological study has showed that gel with carbon dioxide extract of hops is a highly effective drug in treatment of severe and very severe acne vulgaris, characterized by the development of deep and infected wound defects.
Keywords: morphology; complicated wound infection acne vulgaris; experiment; gel with carbon dioxide extract of hops